2012
DOI: 10.5395/rde.2012.37.3.155
|View full text |Cite
|
Sign up to set email alerts
|

Effect of moisture and drying time on the bond strength of the one-step self-etching adhesive system

Abstract: ObjectivesTo investigate the effect of dentin moisture degree and air-drying time on dentin-bond strength of two different one-step self-etching adhesive systems.Materials and MethodsTwenty-four human third molars were used for microtensile bond strength testing of G-Bond and Clearfil S3 Bond. The dentin surface was either blot-dried or air-dried before applying these adhesive agents. After application of the adhesive agent, three different air drying times were evaluated: 1, 5, and 10 sec. Composite resin was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
6
0
1
Order By: Relevance
“…According to the storage, the µTBS of all adhesives agents decreased with time. This may be related to the ability of simplified resin bonding systems to absorb water that plays an important role in hydrolytic degradation of resin-dentin bonds after long-term water storage [16]. Furthermore, the water can infiltrate and decrease the mechanical properties of the polymer matrix by swelling and reducing the frictional forces between the polymer chains, a process is known as "plasticization" [17].…”
Section: Discussionmentioning
confidence: 99%
“…According to the storage, the µTBS of all adhesives agents decreased with time. This may be related to the ability of simplified resin bonding systems to absorb water that plays an important role in hydrolytic degradation of resin-dentin bonds after long-term water storage [16]. Furthermore, the water can infiltrate and decrease the mechanical properties of the polymer matrix by swelling and reducing the frictional forces between the polymer chains, a process is known as "plasticization" [17].…”
Section: Discussionmentioning
confidence: 99%
“…Another advantage of SEAs is the absence of or the low incidence of postoperative sensitivity compared to that with etch-and-rinse systems. [ 7 14 ] It is important for both the investigators and clinicians to elucidate the effect of moisture on the bond strength of adhesive agents. [ 7 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Another study showed that the adhesive agent and the presence of moisture before the application of adhesive agents and the air drying duration affected the bond strength. [ 7 ]…”
Section: Introductionmentioning
confidence: 99%
“…A resistência adesiva de sistemas adesivos autocondicionantes em diferentes condições de umidade e secagem com ar foi estudada por Lee et al 18 , sendo a condição de aplicação de ar em dentina seca, após aplicação do sistema adesivo, a que se mostrou a mais efetiva nesse estudo.…”
Section: Revisão Da Literaturaunclassified